Data visualization of the proportion of youth and adults in Indonesia with computer information technology skills - Septiana Ningtyas; Adi Sopian; Indra Hiswara; Riza Syahrial; Usanto S (Institute of Computer Science (IOCS), 2023)
In the Industrial Revolution 4.0, which integrates information and communication technologies into industry, information and computer technology skills are crucial. These abilities help people use technology and get better jobs. In the increasingly competitive digital age, computer information technology abilities improve a nation's competitiveness globally. These skills can reduce Indonesia's youth and adult unemployment rates. The study visualizes data on the proportion of adolescents and adults with information and computer technology (ICT) skills by province in Indonesia to determine the percentage of equal distribution of ICT skills to improve the quality of human resources in ICT. The data visualization of Adolescents and Adults with Information and Computer Technology Skills (ICT) in Indonesia showed that DI Yogyakarta had the highest percentage at 98.74%, indicating that most of the population has ICT skills. Papua province has the lowest proportion, 33.06%, indicating that most locals lack IT and computer abilities.